ENHANCING ACADEMIC WRITING SKILLS AMONG ECONOMICS STUDENTS: CHALLENGES AND SOLUTIONS (Scientific Conference on Multidisciplinary Studies, 2025)
Academic writing is a crucial skill for economics students, enabling them to express analytical and critical thinking within scholarly discourse. However, many learners face serious challenges when tasked with articulating complex economic concepts, models, and empirical findings due to limited language proficiency. This article analyzes the root causes and implications of these difficulties and proposes practical pedagogical strategies for improving academic writing. The author focuses on key elements such as structured writing, logical argumentation, expressing statistical findings in academic language, adherence to stylistic conventions, and the proper use of scholarly sources. The findings conclude with concrete recommendations aimed at enhancing both instruction and student writing practices.